CRISPR/Cas12a-based approaches for efficient and accurate detection of Phytophthora ramorum - Guo, Yufang; Xia, Hongming; Dai, Tingting; Liu, Tingli; Shamoun, Simon Francis; CuiPing, Wu (Frontiers in Cellular and Infection Microbiology, 2023)
Phytophthora ramorum is a quarantine pathogen that causes leaf blight and shoot dieback of the crown, bark cankers and death on a number of both ornamental and forest trees, especially in North America and northern Europe, where it has produced severe outbreaks. Symptoms caused by P. hibernalis can be confused with those by other Phytophthora and fungal species. Early and accurate detection of the causal pathogen P. ramorum is crucial for effective prevention and control of Sudden Oak Death. In this study, we developed a P. ramorum detection technique based on a combination of recombinase polymerase amplification (RPA) with CRISPR/Cas12a technology (termed RPA-CRISPR/Cas12a). After obtaining DNA, this novel method can be utilized for the molecular identification of P. ramorum using the naked eye, and can specifically detect P. ramorum at DNA concentrations as low as 100pg within 25 min at 37 °C. The system is sensitive for both standard laboratory samples and samples from the field. In summary, we have developed a simple, rapid, sensitive, unaided-eye visualization, RPA-CRISPR/Cas12a-based detection system for the molecular identification of P. ramorum that does not require technical expertise or expensive ancillary equipment.